2019
DOI: 10.3847/1538-3881/ab141b
|View full text |Cite
|
Sign up to set email alerts
|

OGLE-2015-BLG-1670Lb: A Cold Neptune beyond the Snow Line in the Provisional WFIRST Microlensing Survey Field

Abstract: We present the analysis of the microlensing event OGLE-2015-BLG-1670, detected in a high-extinction field, very close to the Galactic plane. Due to the dust extinction along the line of sight, this event was too faint to be detected before it reached the peak of magnification. The microlensing light-curve models indicate a high-magnification event with a maximum of A max 200, very sensitive to planetary deviations. An anomaly in the light curve has been densely observed by the microlensing surveys MOA, KMTNet,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 102 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…Here we analyze OGLE-2018-BLG-0532, whose lensing system contains at least one planet, a cold Neptune with mass ratio = q ´-1.0 0.2 10 4 ( ) , i.e., right at the somewhat arbitrary "low mass-ratio" boundary of Udalski et al (2018) and near the upper end of the possible "pileup" noted by Jung et al (2019). We note that Ranc et al (2019) have reported a planet that also straddles this boundary, with q=(1.00±0.17)×10 −4 . That is, both of these planets would meet the sample conditions of the Jung et al (2019) study.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Here we analyze OGLE-2018-BLG-0532, whose lensing system contains at least one planet, a cold Neptune with mass ratio = q ´-1.0 0.2 10 4 ( ) , i.e., right at the somewhat arbitrary "low mass-ratio" boundary of Udalski et al (2018) and near the upper end of the possible "pileup" noted by Jung et al (2019). We note that Ranc et al (2019) have reported a planet that also straddles this boundary, with q=(1.00±0.17)×10 −4 . That is, both of these planets would meet the sample conditions of the Jung et al (2019) study.…”
Section: Introductionmentioning
confidence: 90%
“…They had argued for a sharp break in the mass-ratio function at q brk ∼0.56×10 −4 and/or a "pile up" of cold Neptunes just above the putative break point. Both of these planets (the other being OGLE-2015Ranc et al 2019), have mass-ratio estimates whose error bars straddle q=1.0×10 −4 . This places them near the upper end of the putative "pileup."…”
Section: Cold Neptunementioning
confidence: 99%
“…We follow a standard empirical error-bar normalization process (Yee et al 2012) intended to estimate proper uncertainties for the lensing parameters in the light-curve modeling. This process, described below, hardly affects the best-fit parameters (Ranc et al 2019). We renormalize the photometric error bars using the formula…”
Section: Data Reductionmentioning
confidence: 99%
“…Finally, we find the final best-fit model fitting all the renormalized light curves. We note that the best-fit model parameters and the final results are not sensitive to moderate changes of the renormalization factors (Ranc et al 2019). The data sets and the renormalization coefficients used in our analysis are summarized in Table 1.…”
Section: Observations and Data Reductionsmentioning
confidence: 99%